Genetic similarity between quince cultivars evaluated by AFLP markers - Manica-Berto, Roberta; Pegoraro, Camila; Mistura, Claudete Clarice; Bresolin, Adriana Pires Soares; Rufato, Andrea De Rossi; Fachinello, José Carlos (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to determine the genetic relationships of 21 quince cultivars based on the amplified fragment length polymorphism (AFLP) marker, for breeding and conservation of genetic resources of the specie in the south of the state of Rio Grande do Sul, Brazil. The DNA from the cultivars was extracted using the CTAB method, and the AFLP reactions were performed with the primers EcoRI/MseI. Two groups were identified among the 21 quince cultivars, one with four and the other with seven cultivars more genetically related. The quince cultivars show high genetic variability, with maximum of 43% similarity.